Going Concern Audit Opinion: Does it Depend on Disclosure and Previous Years’ Audit Opinion? - Kirana, Nanda Wahyu Indah; Simanjuntak , Joshua Christian (PT Global Digital Sains Tekno, 2024)
A going Concern Audit Opinion is an opinion given by an independent auditor to the auditee. This opinion contains the auditor's assessment regarding the company's sustainability. This opinion is one factor that becomes a consideration for management, creditors, investors, and other stakeholders in making decisions. The population in this study were all companies listed on the Indonesia Stock Exchange for the 2017 - 2019 period. The sample selection technique used purposive sampling, and 25 companies were obtained, so 50 samples were processed. Hypothesis testing uses multivariate analysis, namely logistic regression, with E-Views 10 software. This research aims to determine the effect of disclosure and the previous year's opinion on going concern audit opinion with opinion shopping as a moderating variable. This research found that disclosure did not affect the acceptance of going-concern audit opinions. Still, the previous year's opinion positively affected the acceptance of going-concern audit opinions. These results indicate that investors have to be careful in reading the audit opinion of the previous year regarding the company's going concern.